Analysis of Fe metal adsorption in industrial wastewater using adsorbents from betel nut skin - Herlinawati Herlinawati; Junifa Layla Sihombing; Agus Kembaren; Lisnawaty Simatupang; Rika Adhani (Jurnal Pendidikan Kimia (JPKIM), 2023)
This study aims to determine the adsorption ability of betel nut skin-activated carbon on Fe metal in industrial wastewater. Betel nut skin carbon is activated using H2SO4 and HNO3. To identify the quality of adsorption using betel nut skin adsorbents, carbon and activated carbon are characterized using XRD and BET analysis. To determine the concentration of Fe metal adsorbed in the adsorption process, it was analyzed using AAS by determining the optimum conditions for the adsorption of Fe metal from the adsorbent using mass and contact time variations. The XRD characterization results show that betel nut skin carbon activated with sulfuric acid has a higher degree of crystallinity (41.03%) than that activated with nitric acid (20.61%). Betel nut skin activated carbon has a larger pore size of 3.2110 nm than the pore size of betel nut skin carbon of 2.2644 nm. The optimum condition of activated carbon on the adsorption of Fe metal was obtained at a mass of 1 gram with an optimum contact time of 45 minutes. The adsorption capacity of betel nut skin-activated carbon obtained was 1.4174 mg/g and the adsorption efficiency of betel nut skin-activated carbon was 99.84%. The initial concentration of Fe metal obtained was 25.86 ppm, after adding activated carbon from betel nut skin is decreased the concentration of Fe metal obtained was 3.72 ppm. So, the ability of betel nut skin adsorbent to adsorb Fe metal in industrial wastewater was 22.14 ppm.Keywords: Activated carbon; Adsorption; Amorphous; Betel nut skin; Wastewater